Swimming anatomy : your illustrated guide for swimming strength, speed, and endurance - McLeod, Ian (Champaign, Illinois : Human Kinetics, 2010)
"Swimming Anatomy" includes 74 of the most effective swimming exercises, each with step-by-step descriptions and full-color anatomical illustrations highlighting the primary muscles in action and showing how each exercise is fundamentally linked to swimming performance"
Swimming Anatomy provides a stunning visual perspective on swimmers' muscles and how they are developed. The full-color interior contains over 200 expertly drawn illustrations and anatomically grouped exercises with icons identifying the strokes that will benefit most from each exercise to make you faster in the water
1. The swimmer in motion -- 2. Arms -- 3. Shoulders -- 4. Chest -- 5. Abdomen -- 6. Back -- 7. Legs -- 8. Whole-body training
Includes index
Keywords: Aquatic sports injuries; Swimming -- Physiological aspects; Swimming -- Training